2022
DOI: 10.3390/diagnostics12081869
|View full text |Cite
|
Sign up to set email alerts
|

Non-Syndromic Familial Mesiodens: Presentation of Three Cases

Abstract: Mesiodens are the most common supernumerary teeth and are detected incidentally during routine radiographic examination, so late diagnosis complications are very common. The dentist must make a timely diagnosis and thus avoid clinical complications. Despite advances in knowledge of dental morphogenesis and differentiation, the etiology of mesiodens remains unclear. Therefore, several theories have been postulated to explain how and why they develop. It was described in the literature that heredity could play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The patient in this case mentioned his aunt and grandmother having a mesiodens tooth like him. In a study by Alarcón J. et al (2022), three cases were examined using CBCT to confirm the presence of inherited mesiodens, highlighting the hereditary nature of this dental anomaly [7]. Mesiodens were present for three generations in this case study, involving a grandmother, her daughter, and her grandson, highlighting the strong familial inheritance of genetic factors associated with mesiodens [7].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The patient in this case mentioned his aunt and grandmother having a mesiodens tooth like him. In a study by Alarcón J. et al (2022), three cases were examined using CBCT to confirm the presence of inherited mesiodens, highlighting the hereditary nature of this dental anomaly [7]. Mesiodens were present for three generations in this case study, involving a grandmother, her daughter, and her grandson, highlighting the strong familial inheritance of genetic factors associated with mesiodens [7].…”
Section: Discussionmentioning
confidence: 70%
“…Extraction is the primary treatment for mesiodens due to the pathologies and alignment disturbances they cause in the dentition, which can lead to further complications if left untreated such as increased risks of infection, malocclusion, and damage to neighboring teeth [7][8][9]. Studies have consistently shown that mesiodens can lead to complications such as crowding, spacing issues, and the rotation of adjacent teeth, which can significantly impact dental alignment and function, according to the findings of these studies [1][2][3]9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their appearance, mesiodens can be classified as rudimentary mesiodens and supplementary mesiodens in permanent and deciduous dentition, respectively. They are termed conical, tuberculate, or molariform based on their morphology [ 21 ].…”
Section: Discussionmentioning
confidence: 99%